Aplikasi Pengendali Kamera DSLR Nirkabel Tipe Low End Berbasis Android - Endang Tirtana; Eko Budi Setiawan (Ultima Computing : Jurnal Sistem Komputer, 2017)
One of those beneficial innovations in DSLR camera it is able to connect with other mobile devices using wireless network. Its primary function is to control camera from distance and to instantly upload photos to social medial. But, not all DSLR cameras are equipped with this feature. Only the latest mid-end and high-end DSLR camera have the feature. In order to solve the previously mentioned issue, the researcher conducted a trial using Arduino and Bluetooth as the camera’s wireless network. The result showed that Arduino did not have its own module and, as a result, users would need to add new modules if they wanted to add new features. This was considered ineffective and inefficient. Moreover, Bluetooth connection is rarely used nowadays due to the limited transfer rate and area coverage compare to using WiFi connection. In line with the aforementioned explanation, a research was held with the main objective to access and operate low-end DLSR camera using Raspberry Pi. The Raspberry Pi was operated using access point and controlled by smartphone. Index Terms— Camera, DSLR, wireless, Raspberry Pi, Android